PENGARUH CITRA MEREK , PROMOSI DAN INFLUENCER MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK SLAI OLAI DI KOTA BATAM - Indra, Meylani; Hikmah (SCIENTIA JOURNAL, 2025)
This study aims to analyze the influence of brand image, promotion, and influencer marketing on purchasing decisions for Slai Olai products in Batam City. The sample in this study amounted to 204 respondents obtained through purposive sampling method, with data collection techniques using questionnaires. Data analysis was carried out using the SPSS version 26 application, which includes data quality testing, classical assumption testing, influence testing, and hypothesis testing. The analysis method used in this study is multiple linear regression. The results of the study indicate that the variables of brand image, promotion, and influencer marketing partially and simultaneously have a positive and significant effect on purchasing decisions for Slai Olai products in Batam City. Based on these findings, the results of this study are expected to be the basis for consideration for companies in formulating more appropriate marketing strategies to increase consumer purchasing decisions.